Changes in some chemical properties of inceptisol soil and growth of maize (Zea mays L.) due to durian skin compost and SP36 fertilizer - Anggra Purma Tarigan; Supriadi; Alida Lubis (Talenta Publisher, 2018)
Inceptisol is a widely enough soil and has many obstacles to use as agricultural field, some of the constraints are; Low level of the organic content, soil acidity, high level of Al saturation and low CEC hance this land cause a lower productivity. increasing its productivity by giving organic material compost which is durian skin compost and SP36 fertilizer.This research is aimed to know the change of some chemical properties of Inceptisol soil and growth of corn plant (Zea mays L.) due to composting of durian skin and SP36 fertilizer. This study was conducted by using Randomized Block Design (RBDs) method with two replications consisting of thirty two treatments. The treatments divided in two addition fertilizer durian skin compost (B) and SP36 (P) fertilizer consisting of; 0 g / polybag (B0), 12.5 g / polybag (B1), 25 g / polybag (B2), 37.5 g / polybag (B3), 0 g / polybag (P0), 0,25 g / polybag (P1), 0,50 g / polybag (P2), 0.75 g / polybag (P3), and their interactions. The results showed that durian skin compost significantly affected the carbon content on soil, and SP36 fertilizer had significant effect on soil P level, and both interaction had significant effect on the height of plant.